2021
DOI: 10.1155/2021/5553486
|View full text |Cite|
|
Sign up to set email alerts
|

Experimental Study on the Correlation between miRNA-373 and HIF-1α, MMP-9, and VEGF in the Development of HIE

Abstract: Introduction. Microribonucleic acids (miRNAs) have short (approximately 18 to 25) nucleotides and are evolutionarily conserved and endogenously expressed RNAs belonging to a family of noncoding RNA molecules. miRNA-373 regulates cell proliferation, migration, apoptosis, invasion, and repairing damaged DNA after hypoxia stress. Neonatal hypoxic–ischemic encephalopathy (HIE) refers to perinatal asphyxia caused by partial or complete hypoxia, reduced or suspended cerebral blood flow, and fetal or neonatal brain d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Studies in infants with HIE have shown that levels of miR-374a, miR-376c, miR-161b, and miR-181b are decreased in umbilical cord blood (which contains the highest level and activity of RNase1 compared to other blood sources) and could distinguish infants affected by perinatal asphyxia or HIE from healthy infants (Looney et al, 2015(Looney et al, , 2019O'Sullivan et al, 2019). Meanwhile, miR-373 was found to be increased and positively correlates with levels of VEGF, MMP-9, and HIF-1α in infants with HIE (Liu et al, 2021), while miR-210 exhibits increased levels in a piglet model of global hypoxia (Garberg et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Studies in infants with HIE have shown that levels of miR-374a, miR-376c, miR-161b, and miR-181b are decreased in umbilical cord blood (which contains the highest level and activity of RNase1 compared to other blood sources) and could distinguish infants affected by perinatal asphyxia or HIE from healthy infants (Looney et al, 2015(Looney et al, , 2019O'Sullivan et al, 2019). Meanwhile, miR-373 was found to be increased and positively correlates with levels of VEGF, MMP-9, and HIF-1α in infants with HIE (Liu et al, 2021), while miR-210 exhibits increased levels in a piglet model of global hypoxia (Garberg et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Limd1, a LIM domain-containing protein, has been extensively studied in various cancers, where it has shown negative effects on tumor growth (Foxler et al 2018 ; Zhou et al 2019a , b ; Huggins et al 2017 ; Huggins and Andrulis 2008 ; Sharp et al 2008 ; Liu et al 2021 ). However, its involvement in HIBD has been largely unexplored.…”
Section: Discussionmentioning
confidence: 99%
“…This neurotrophin, secreted by central nervous system neurons and astrocytes, is involved in neuronal survival and synaptic plasticity [ 46 , 47 ]. Liu et al [ 68 ] also showed an increase in serum matrix metalloproteinase-9 (MMP-9) in neonates with HIE. MMP-9 is involved in the disruption of the blood–brain barrier by degrading brain vasculature basement membrane components [ 47 ].…”
Section: Proteomicsmentioning
confidence: 99%